Impact of nanoconfinement on the physical state and conductivity mechanisms of a 2-picolinium ionic liquid crystal - Santos, Andreia F. M. (2024)
Funding Information: This work was supported by the Associate Laboratory for Green Chemistry LAQV ( UID/QUI/50006/2019 ), i3N (UID/ CTM / 50025/2019 ) and CeFEMA (UID/ CTM / 04540/2019 ), which are financed by national funds from FCT- MCTES and by FEDER funds through the COMPETE 2020 Program. The authors also thank the National Funds through FCT- MCTES and POR Lisboa 2020, under the project numbers PTDC/EAM - AMB / 2023/2021 ( SUSTECH4H2O ), POCI-01-0145-FEDER-007688 and European Interdisciplinary Action ( COST Action CA21159 , PhoBioS). A. F. M. Santos also acknowledges FCT- MCTES for the PhD Grant ( SFRH/BD/132551/2017 ) and I. Matos for the contract CEECIND/004431/2022 . Funding Information: This work was supported by the Associate Laboratory for Green Chemistry LAQV, Portugal, (LA/P/0008/2020, UIDB/50006/2020, UIDP/50006/2020), i3N, Portugal, (LA/P/0037/2020, UIDB/50025/2020, UIDP/50025/2020), CQE, Portugal, (UIDB/00100/2020, UIDP/00100/2020) and CeFEMA, Portugal, (UIDB/04540/2020, UIDP/04540/2020), which are financed by national funds from FCT-MCTES, Portugal, and by FEDER funds through the COMPETE 2020, Portugal, Program. The authors also thank the National Funds through FCT-MCTES, Portugal and POR Lisboa 2020, under the project numbers PTDC/EAM-AMB/2023/2021 (SUSTECH4H2O), POCI-01-0145-FEDER-007688 and European Interdisciplinary Action (COST Action, Belgium, CA21159, PhoBioS). A. F. M. Santos also acknowledges FCT-MCTES, Portugal, for the PhD Grant (SFRH/BD/132551/2017) and I. Matos for the contract CEECIND/004431/2022. Publisher Copyright: © 2024 The Author(s)